Tissue selection and the optimization of the DNA isolation method for the construction of genomic library of red dragon fruit (Hylocereus polyrhizus) / Daniel Lee Kian Poh - Lee, Daniel Kian Poh (2013)
Genomic library of Hylocereus polyrhizus was constructed in bacteriophage Lambda Fix II with 20kb inserts. DNA of the H. polyrhizus that was used to construct the genomic library was obtained from young germinated seeds’ leaves. The tender and partially expended leaves were selected. Seed germination was also carried out to select the best time to harvest leaves for DNA extraction. Different treatment for seeds affects the germination and growth of the seed and acid washed seeds germinated in light condition the best. DNA extraction was modified in order to obtain pure and high yield DNA for genomic library construction. Restriction enzyme (BamH I) used to digest the selected fragment from the total DNA and analysed on a gel electrophoresis. Phenolchloroform method used to purify insert DNA successfully yielded high concentration insert DNA which is a very crucial step in constructing genomic library. Plaques formed indicated that the bacteriophage has successfully lysised the cells. In this study, 80 – 100 plaques per Petri dish formed showed bacteriophage has successfully lysised the cells and indicated that a good genomic library has been established. This genomic library can be use for further study such as fish out important gene and study the gene interaction.